A study of coupled interfacial reactions and diffusion in multi-component metallic/ionic systems - Ma, Dongke Duncan (My University, 1992)
A study consisting of theoretical and experimental work on kinetics of simultaneous interfacial reactions in multi-component metallic/ionic systems has been carried out in the present work. General rate expressions for simultaneous interfacial reactions are proposed based on the application of mass action law to the electrodic half-cell reactions and the constraint of no net electric current. The nature of coupling among interfacial reactions is discussed by defining the coupling factor which is a collective property of the system, contributed by and common to all interfacial reactions. Kinetic behavior of each element can be individually and simultaneously described. Experimental work is conducted in slag/metal system for the study of coupled interfacial reactions and diffusion. Considering interfacial reactions as the boundary conditions for diffusion in both phases, a mathematical model is developed. Computed results, based on thermochemical parameters mostly reported in the literature, are compared with diffusion profiles measured by electron probe microanalysis (EPMA) in silicate slag and Fe-Mn-Si alloy at 1763$\sp\circ$K. Values of reaction rate constants for transfer of iron, manganese and silicon are recommended through curve fitting with the experimental data. The conventional pseudo-binary approach in the formulation of rate equations for interfacial reactions in multi-component slag/metal systems may be deduced from the present theory with simplifying assumptions and as a limiting case.
Keywords: Materials Science and Engineering; Materials Science and Engineering